2020
DOI: 10.1103/physrevmaterials.4.024402
|View full text |Cite
|
Sign up to set email alerts
|

Computational screening of magnetocaloric alloys

Abstract: An exciting development over the past few decades has been the use of high-throughput computational screening as a means of identifying promising candidate materials for a variety of structural or functional properties. Experimentally, it is often found that the highest-performing materials contain substantial atomic site disorder. These are frequently overlooked in high-throughput computational searches however, due to difficulties in dealing with materials that do not possess simple, well-defined crystallogr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…4 A survey of magnetocalorics based on density functional theory calculations has established a broad correlation between magnetostructural coupling (approximated using magnetic deformation calculations) and MCE in materials with both first-order and continuous transitions. 11,12,19,20 This work made the prediction that AlFe 2 B 2 , among some other materials with strong magnetocaloric effects observed at continuous magnetic transitions, would display strong magnetostructural coupling when investigated experimentally. AlFe 2 B 2 was first isolated and its crystal structure solved by Jeitschko in 1969.…”
mentioning
confidence: 82%
“…4 A survey of magnetocalorics based on density functional theory calculations has established a broad correlation between magnetostructural coupling (approximated using magnetic deformation calculations) and MCE in materials with both first-order and continuous transitions. 11,12,19,20 This work made the prediction that AlFe 2 B 2 , among some other materials with strong magnetocaloric effects observed at continuous magnetic transitions, would display strong magnetostructural coupling when investigated experimentally. AlFe 2 B 2 was first isolated and its crystal structure solved by Jeitschko in 1969.…”
mentioning
confidence: 82%
“…It has been suggested that promising candidate materials for magnetic refrigeration via the magnetocaloric effect can be evaluated through a computational proxy known as magnetic deformation, or Σ M [9,10]. This proxy is a predictor of the strength of magnetostructural coupling in a given material calculated using density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…We suspect such compounds can exhibit signicant DS M upon second order phase transition at the corresponding Curie temperature, which will be saved for detailed investigation in the future. Additionally, isostructural doping can be applied to improve the magnetocaloric performance 80 or to ne tune the magnetostructural or metamagnetic transitions, 81 which enables further design of magnetocaloric materials with optimal performance.…”
Section: Magnetic Propertiesmentioning
confidence: 99%